Rancang Bangun Website Order Pada Bagian Bonding Agent Di Mold Departement PT. RCI - Faishal Hizbullaah; Suharyanti; Kuswantori, Ari (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
The rapid advancement in information technology (IT) has prompted various industrial sectors to adoptdigitalization to enhance efficiency and productivity. PT. RCI, a manufacturing company in Indonesia, faceschallenges with time-consuming and error-prone manual ordering and monitoring processes. This study aims toaddress these issues by designing and building a website-based order insert system. The digitalization process isexpected to reduce ordering time, improve operational efficiency, and minimize errors. The methods used includeUnified Modeling Language (UML) modeling, with application development employing the CodeIgniterframework and PostgreSQL database. The study results indicate that digitalization and the use of informationtechnology can improve data management efficiency and effectiveness. The implementation of this system isanticipated to bring significant improvements to PT. RCI's production processes and provide broader benefits tothe manufacturing industry.